Impact of Marketing Strategies on Brand Loyalty - Dorica Apayi (Uganda Christian University, 2024)
This research the impact of marketing strategies on brand loyaltyin Uganda. The study adopted a cross-sectional survey design to sample for the study. This method involved random selection of respondents who were dministered with questionnaires. Relevant conceptual, theoretical and empirical literature was reviewed. The target population of the study comprised selected customers in selected firms in Uganda. The questionnaire administered was three hundred and ten (310) copies and three hundred copies (300) retrieved which constitute the sample size. Findings revealed that there is a significant impact of marketing strategies on brand loyalty. The finding of the study also reveals that intense competition makes it challenging to develop marketing strategies that differentiate a brand and foster loyalty. In addition, the finding of the study also reveals that building strong relationships with customers through personalized interactions and tailored offerings is one of the most effective marketing strategies used by businesses to build brand loyalty.The findings of the study also reveal that there is a significant relationship between marketing strategies and brand loyalty. The finding of the study also reveals that creating memorable experiences for customers, such as events, webinars, or workshops, to build brand affinity is one of the most effective marketing strategies used by businesses to build brandloyalty. The findings of the study reveal that marketing strategies can directly influence brand loyalty by creating emotional connections, building trust, and providing value to customers. It was therefore concluded that marketing strategies is significantly related to brand loyalty in Uganda. It was recommended that businesses should develop comprehensive marketing strategies that incorporate a variety of techniques, such as digital marketing, content marketing, and social media engagement. A holistic approach will ensure a wider reach and more significant impact on brand loyalty.
Undergraduate Research